Prospective Register Of patients undergoing repeated OFfice and Ambulatory Blood Pressure Monitoring (PROOF-ABPM): protocol for an observational cohort study. Issue 10 (31st October 2016) - Sheppard, James P; Martin, Una; Gill, Paramjit; Stevens, Richard; McManus, Richard J
Abstract : Introduction: The diagnosis and management of hypertension depends on accurate measurement of blood pressure (BP) in order to target antihypertensive treatment appropriately. Most BP measurements take place in a clinic setting, but it has long been recognised that readings taken out-of-office (via home or ambulatory monitoring) estimate true underlying BP more accurately. Recent studies have shown that the change in clinic BP over multiple readings is a significant predictor of the difference between clinic and out-of-office BP. Used in combination with patient characteristics, this change has been shown to accurately predict a patient's out-of-office BP level. The present study proposes to collect real-life BP data to prospectively validate this new prediction tool in routine clinical practice. Methods and analysis: A prospective, multicentre observational cohort design will be used, recruiting patients from primary and secondary care. All patients attending participating centres for ambulatory BP monitoring will be eligible to participate. Anonymised clinical data will be collected from all eligible patients, who will be invited to give informed consent to permit identifiable data to be collected for data linkage to external outcome registries. Descriptive statistics will be used to calculate the sensitivity, specificity, positive and negative predictive values of the out-of-office BP prediction tool. Area under the receiver operator characteristic curve statistics will be used to examine model performance. Ethics and dissemination: Ethical approval for this study has been obtained from the National Research. Ethics Service Committee South Central—Oxford A (reference; 15/SC/0184), and site-specific R&D approval has been acquired from the relevant NHS trusts. All findings will be presented at relevant conferences and published in peer-reviewed journals, on the study website and disseminated in lay and social media where appropriate.